A liposome preparation based on β-CD-LPC molecule and its application as drug-delivery system. (24th September 2018) - Cai, Anran; Wang, Chunhua; Yan, Miaomiao; Ma, Liying; Liu, Wenbo; Li, Feng; Liu, Tongshen; Song, Peng; Gao, Zonghua; Li, Jing; Xin, Meixiu; Wei, Guangcheng
Aim: The β-CD-LPC molecule was synthesized based on the conjugation of LPC and β-CD molecules and it could self-assemble into liposome which was used to encapsulate the Dox to form nanomedicine for the cancer therapy.Materials & methods: The anticancer and antitumor effect of β-CD-LPC-Dox nanomedicine was studied with the vitro and vivo experimental methods.Results: The result showed that β-CD-LPC liposome had high Dox drug-loading rate and a good sustained-release effect. Cell experiment showed that the β-CD-LPC-Dox nanomedicine could effectively induce cancer cell apoptosis and in vivo experiments showed that β-CD-LPC-Dox liposome could effectively inhibit tumor growth and had an effective anticancer activity with lower biotoxicity.Conclusion: The β-CD-LPC-Dox nanomedicine could be applied as a candidate drug to therapy the cancer.